Risk Factors for Death in Bangladeshi Children Under 5 Years of Age Hospitalized for Diarrhea and Severe Respiratory Distress in an Urban Critical Care Ward - Tahmina Alam MBBS (Global Pediatric Health, 2017)
Children with diarrhea hospitalized for respiratory distress often have fatal outcome in resource-limited settings, although data are lacking on risk factors for death in such children. We sought to evaluate clinical predictors for death in such children. In this prospective cohort study, we enrolled under-5 children with diarrhea admitted with severe respiratory distress to the intensive care unit of Dhaka Hospital of International Centre for Diarhoeal Disease Research, Bangladesh, from September 2014 through September 2015. We compared clinical and laboratory characteristics between study children those who died (n = 29) and those who survived (n = 62). In logistic regression analysis, after adjusting for potential confounders, the independent predictors for death in children hospitalized for diarrhea and severe respiratory distress were severe sepsis and hypoglycemia ( P < .05 for all). Thus, recognition of these simple parameters may help clinicians identify children with diarrhea at risk of deaths in order to initiate prompt management for the better outcome, especially in resource-poor settings.